THE IMPACT OF BENIGN PROSTATE HYPERPLASIA TREATMENT MODALITIES ON THE INCIDENCE AND PROGRESSION OF URETHRAL STRICTURE : A COMPREHENSIVE SYSTEMATIC REVIEW - Dwitawira Wibowo, Nanchita; Rizky Hidayat, Muhammad (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2024)
Background: Urinary tract symptoms in elderly men are frequently caused by BPH, which frequently results in urethral stricture. Perioperative morbidity might result from surgical methods such as simple open prostatectomy and transurethral resection. Several techniques, such as HoLEP, have surfaced as novel therapies. Methods: Following PRISMA 2020 guidelines, this systematic review concentrated on full-text English literature published between 2014 and 2024. Editorials and review articles that appeared in the same journal as the submission were not accepted without a DOI. The literature was assembled using a variety of online databases, including ScienceDirect, PubMed, and SagePub. Result: The study utilized reliable sources like Science Direct, SagePub, and PubMed for screening over 500 publications. Six papers were identified as relevant for systematic analysis, followed by further study and examination of the complete document. Conclusion: The treatment of BPH patients using the TURis system and TUEP is effective in preventing postoperative complications like urethral strictures. However, further large-scale multicentre RCTs are needed to confirm these findings. BMA is suitable for short proximal bulbar urethral strictures, and the inverted omega En-bloc HoLEP technique is safe and effective for all prostate sizes.